INFLUENCE OF VEGETATION ON SOIL CARBON STOCKS IN FORESTS (REVIEW) - A. I. Kuznetsovа (Вопросы лесной науки, 2021)
Existing estimates of carbon stocks in taiga and coniferous-deciduous forests show that almost half of the total organic carbon in these ecosystems is accumulated in forest soils. Vegetation as the main source of organic matter in the soil, interact with soil biota, which processes plant litter, and with abiotic environmental factors, determines the processes of formation and accumulation of soil organic matter. Changes in the composition of vegetation are the driver of the dynamics of soil carbon stocks; however, insufficient attention has been paid to the analysis of this issue. The review analyzes the main ways of transferring carbon from the vegetation pool to the soil pool and the influence of three main predictors of vegetation that affect the carbon stock in soils: the amount and quality of litter of individual species (species identity) of plants and the structural diversity of the plant community; gaps in knowledge and the ways of development of this scientific direction are proposed.